Entrepreneurial orientation and new venture performance in emerging markets: the mediating role of opportunity recognition - Muhammad Anwar; Thomas Clauss; Wunnam Basit Issah (Review of Managerial Science, 2021)
How entrepreneurial orientation facilitates the identification of new opportunities in newly established ventures in emerging economies remains largely unexplored. Approaching entrepreneurial orientation as a second order latent construct, we examined the mediating role of opportunity recognition on new venture performance. Using a survey data from 316 SMEs, the results of the analysis in SmartPLS highlights that entrepreneurial orientation indirectly contributes to the performance of new ventures, where the relationship is partially mediated by opportunity recognition. The findings show that firms with high entrepreneurial orientation can identify and exploit new opportunities as well as enjoy superior performance.
Keywords: L26; M13; M16; 650; Entrepreneurial orientation; Opportunity recognition; New venture performance; Sensing capacity